2004
DOI: 10.1063/1.1777819
|View full text |Cite
|
Sign up to set email alerts
|

Decay mechanisms of a blue organic light emitting diode

Abstract: A blue organic light-emitting diode employing perylene as light emitting dopant and 9,10-bis(3’5’-diaryl)phenyl anthracene (DPA) as host has been studied for its decay mechanisms. The device structure is ITO(indium tin oxide)∕CuPc(copper phthalocyanine)∕NPD(α-naphthylphenylbiphenyl diamine)∕DPA:perylene∕Alq3 (8-hydroxy-quinoline aluminum)∕MgAg. In this device, CuPc and NPD are used as hole injection and transporting layers, DPA as a blue host, perylene as a blue emitting dopant, Alq3 as an electron transport l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Even at an initial luminance of 1000 cd/m 2 , the lifetime is as long as 30920 h. To the best of our knowledge, this is the first hybrid WOLED with long lifetime in the revealed literature so far. Since the half lifetimes for TVs applications must be about 100000 h 30 , it is obviously seen that our device can satisfy this practical demand. On one hand, although all-fluorescent WOLEDs can exhibit long lifetime over 150000 h at 1000 cd/m 2 , the maximum efficiency is only 14.7 cd/A because the triplet excitons cannot be harvested 34 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Even at an initial luminance of 1000 cd/m 2 , the lifetime is as long as 30920 h. To the best of our knowledge, this is the first hybrid WOLED with long lifetime in the revealed literature so far. Since the half lifetimes for TVs applications must be about 100000 h 30 , it is obviously seen that our device can satisfy this practical demand. On one hand, although all-fluorescent WOLEDs can exhibit long lifetime over 150000 h at 1000 cd/m 2 , the maximum efficiency is only 14.7 cd/A because the triplet excitons cannot be harvested 34 .…”
Section: Resultsmentioning
confidence: 96%
“…Finally, since the device lifetime is essential to practical use 30 31 32 , we have measured the lifetime of W6. As shown in figure 4b , a half lifetime of 75.9 h at an initial luminance of 10000 cd/m 2 is obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The E LUMO is very close to the widely used organic green emitter, tris-(8-hydroxyquinolinato)-aluminium (Alq 3 ) whose OLEDs have been optimized to give a high external quantum efficiency of ∼12% at 100 Cd/m 2 . 12…”
Section: Characterization Of Cf3-dpamentioning
confidence: 99%
“…About a couple of years back, a new series of undoped 9,10-DPA-based blue fluorophores was synthesized with bulky substituents which showed much higher EQE of 4.5% 11 as compared to unsubstituted DPA (EQE-1.5%) or doped 9,10-DPA (EQE ∼ 2%). 12 Subsequently, several attempts were made to improve the emission and thin film properties of anthracene derivatives. [13][14][15][16][17][18] It was demonstrated that the film forming properties of DPA can be improved by introducing bulky aryl substituents at the 2-and 6-positions of anthracene (instead of the 9-and 10positions).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lifetime of the organic devices remains a major challenge that must be overcome before the wide application of WOLED technology 4. For example, the television application requires a lifetime of at least 100 000 h at video brightness without noticeable color shift 5. As reported by Kodak researchers, WOLEDs with high correlated color temperatures (CCT) are favored for display application, which requires a significant amount of blue contribution in the white emission 6.…”
Section: Introductionmentioning
confidence: 99%